Recommendations for sex/gender neuroimaging research: key principles and implications for research design, analysis, and interpretation - Rippon, Gina; Jordan-Young, Rebecca; Kaiser, Anelis; Fine, Cordelia (Frontiers in Human Neuroscience, 2014)
For over a decade, neuroimaging (NI) technologies have had an increasing impact in the study of complex cognitive and social processes. In this emerging field of social cognitive neuroscience, a central goal should be to increase the understanding of the interaction between the neurobiology of the individual and the environment in which s/he develops and functions. The study of the relationship between sex and gender could offer a valuable example of such research. We identify here four main principles that should inform NI research. First, the principle of overlap, arising from evidence of significant overlap of female/male distributions on measures of many gendered behaviours. Second, the principle of mosaicism, arising from evidence that for both behaviour and brain, each individual manifests a complex and idiosyncratic combination of feminine and masculine characteristics. Third, the principle of contingency, arising from evidence that female/male behavioural differences are contingent on time, place, social group and context. Fourth, the principle of entanglement, arising from an awareness that the neural phenotypes that NI techniques measure are a function of the interactive and reciprocal influence of biology and environment. These important principles have emerged and become well-established over the past few decades, but their implications are often not reflected in the design and interpretation of NI sex/gender research. We therefore offer a set of guidelines for researchers to ensure that NI sex/gender research is appropriately designed and interpreted. We hope this ‘toolkit’ will also be of use to editorial boards and journal reviewers, as well as those who view, communicate and interpret such research.